Pengukuran Ketebalan Lapisan Metal Pada Plastik Berbasis Sensor Inframerah - Yaya Finayani; Muhammad Alhan; Sunaryo; Sudarno (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Plastic metalization process is carried out by heating the aluminum to its melting point in a vacuum so that the atoms and molecules will be evaporate and stick on to the plastic surface, then forming thin layer accross its surface. PT. Tomoko Daya Perkasa is one of the companies who performs plastic metalization. In doing this process, the company uses rewind machine and metallizing machine. PT. Tomoko Daya Perkasa uses OD-Meter to measure metal coating thickness. This tool is not embedded on the metallization machine. Therefore, a tool that can be mounted directly to metallizing machine is needed to monitor the thickness during the process of metalization. The metal layer thickness gauges are designed using the GP2Y1010AU0F infrared sensor and TSL2561 infrared receiver. Arduino and VB-NET software are used to create the program of the tool. Laboratory test and rewind machine test results show measurement errors of 0.3% and 1.9%, respectively. These error values are still acceptable, because the maximum limit of tolerance applied in PT. Tomoko Daya Perkasa is about 2.5%. In conclusion, the tool works well and can be used as expected.